A study of the pointed observation methods and sensitivity of HXMT - 金晶 陈勇 张双南 张澍 李新乔 李刚 (Chinese physics C, 2010)
The Hard X-ray Modulation Telescope （HXMT） is an X-ray astronomy satellite consisting of three slat-collimated instruments, the High Energy X-ray Instrument （HE）, the Medium Energy X-ray Instrument （ME）, and the Low Energy X-ray Instrument （LE）. HXMT will carry out an all sky survey and make pointed observations in the 1-250 keV energy band. In order to get the source and background fluxes simultaneously in the pointed observations, two methods, i.e., the combined field of view （FOV） method and the off-axis pointing method are proposed in this paper. Comprehensive analyses of the sensitivities of the three instruments by using these two methods are presented, respectively. It is found that the off-axis pointing method has a higher sensitivity for HE and ME but a lower sensitivity for LE. Since the axes of the three instruments are aligned along the same direction, the off-axis pointing method is recommended as the main method in the pointed observation for HXMT; the combined FOV method can be used when LE is the most relevant instrument in order to satisfy the scientific objective of the observation.